Cultural diversity and sensitivity in public estate renewals: evidence from an Australian longitudinal study. Issue 6 (2nd July 2020) - Liu, Edgar; Blunden, Hazel
Abstract: Social mixing has been part of government policies regarding estate renewals in many countries. It is mostly achieved through tenure diversification, such as introducing privately owned and rented dwellings. Concurrently, in many residualized social housing sectors, larger shares of tenants now have high and complex needs, including recently settled refugees. Therefore, social and spatial manifestations of multiculture have become more complex. Consequently, a non-tenure-related form of social mixing, primarily one of cultural difference, occurs. This article considers the unintended effects of wider policies around resettlement of refugees in the context of estate renewal. Considering Wacquant et al. 's (2014, Territorial stigmatization in action, Environment and Planning A: Economy and Space, 46, pp. 1270–1280) discussions of dissimulation and microdifferences, it reflects on the experiences of residents living on estates that are currently undergoing renewal in suburban Adelaide, South Australia, and reports on tensions that sometimes emerge between long-established and more recently settled residents as well as efforts (by managing authorities, support services and the residents) to foster cross-cultural engagement and cultural sensitivity on these estates.